2008
DOI: 10.1007/s11095-008-9625-0
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Nanosuspensions into Dry Powders by Spray Drying: A Case Study

Abstract: Purpose. Drying of nanosuspensions can cause destabilization of the particles, leading to irreversible aggregation. In order to prepare an effective solid dosage form for a nanosuspension, it is imperative that the spray-dried nanoparticles should go back to their original particle size when reconstituted in an aqueous system. This case study examines impact of various formulation and processing parameters on redispersibility of the spray dried nanoparticles. Methods. Nanosuspensions were prepared using the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(92 citation statements)
references
References 18 publications
2
90
0
Order By: Relevance
“…The nanosuspension pellets showed dissolution profiles similar to those of the original drug nanosuspensions, but with a delay of 3 minutes, which could be explained by the fact that reconstitution of the compactly coated pellets took longer. 33,34 It is concluded that the dissolution capacity of the original nanosuspensions was preserved in the solidified nanosuspensions.…”
Section: In Vitro Dissolutionmentioning
confidence: 99%
“…The nanosuspension pellets showed dissolution profiles similar to those of the original drug nanosuspensions, but with a delay of 3 minutes, which could be explained by the fact that reconstitution of the compactly coated pellets took longer. 33,34 It is concluded that the dissolution capacity of the original nanosuspensions was preserved in the solidified nanosuspensions.…”
Section: In Vitro Dissolutionmentioning
confidence: 99%
“…Such a coating would have created particle repulsions during spray-drying and inhibited the irreversible aggregation of particles. 28 However, 1% of NaTau (w/w of ITZ) seemed to insufficiently cover the entire surface of the particles and did not provide a sufficiently large charge load on the particle surfaces. Therefore, a light agglomeration still SD mannitol occurred in formulation N3.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…Recently, the spray dried nanosuspension of itraconazole was prepared. 9) The emphasis was to examine the impact of various formulation and processing parameters on redispersibility of the spray dried nanoparticles and in-vitro dissolution. The in-vivo study was not performed to demonstrate the bioavailability enhancement by nanosuspension.…”
mentioning
confidence: 99%